Analisis Pengaruh Sikap, Norma Subyektif, Dan Kontrol Perilaku Yang Dirasakan Terhadap Minat Beli Produk Private Brand Alfamart Di Sekitar Universitas Muhammadiyah Surakarta - WIBOWO, Amanda Anidia Ita, Soepatini, SE.,M.Si.,Ph.D (2016)
ABSTRACT The purpose of this study was to analyze the influence of attitude (X1), sujective norms (X2), and perceived behavioral control (X3) on buying interest (Y) private brand alfamart in the University Muhammadiyah of Surakarta area. The population in this study were all students of the Faculty of Economic and Business University Muhammadiyah of Surakarta. Sampling technique used was purposive sampling by taking the 100 respondents in accordance with predetermined criteria. This study uses multiple linier regression test (ttest,Ftest, and R2 test). This research resulted in several findings, the first findings was attitude positive and significant impact on the buying interest of private brand products alfamart. the second discovery, subjective norms positive and significant impact on the buying interest of private brand product alfamart. Third, perceived behavioral control was not significant on the buying interest of private brand products alfamart. This study advises companies to draw up strategies so that consumers buying interest will be increased.